Potassium in Human Health - Tang, Jie (Physiology, 2022)
This is an introductory book on the role of potassium in health, physiology of potassium homeostasis, diagnostic approach to potassium derangement, and clinical management of potassium disorders. It is a concise, easy-to-read reference for students in the health professions, mid-level providers, house staff trainees, and clinicians.